Home Lab: Exciting Experiments for Budding Scientists - Robert Winston (London Dorling Kindersley Limited, 2016)
Winner of the Royal Society's Young People's Book Prize 2017, this jam-packed collection of fun and simple science experiments for kids is perfect for the classroom or home. Stir up some sticky slime, build a Solar System with rubber bands, power a speed boat using soap, and construct an erupting volcano, all with Home Lab, which offers exciting experiments for budding scientists. Including a foreword by Professor Robert Winston, this stunning book includes 28 brilliant science projects, using clear step-by-step instructions, everyday ingredients that can be found around the house, and amazing photography to guide you from start to finish. Plus fact-filled panels explain the science behind every experiment, and real-world examples provide a context to better understand scientific principles. Perfect for budding scientists and crafters, Home Lab will keep children entertained for hours. This is the UK edition of the US title Maker Lab.